New Perspectives on Atherogenic Dyslipidaemia and Cardiovascular Disease - Alberto J Lorenzatti; Peter P Toth (European Cardiology Review)
Over the past few decades, atherogenic dyslipidaemia has become one of the most common phenotypic presentations of lipid abnormalities, being strongly and unequivocally associated with an increased risk of cardiovascular (CV) disease. Despite the excellent results achieved from statin and non-statin management of LDL cholesterol and CV events prevention, there still remains a significant residual risk, associated with the prevalence of non-LDL cholesterol lipid patterns characterised by elevated triglyceride levels, low HDL cholesterol, a preponderance of small and dense LDL particles, accumulation of remnant lipoproteins and postprandial hyperlipidaemia. These qualitative and quantitative lipid modifications are largely associated with insulin resistance, type 2 diabetes and obesity, the prevalence of which has grown to epidemic proportions throughout the world. In this review, we analyse the pathophysiology of this particular dyslipidaemia, its relationship with the development of atherosclerotic CV disease and, finally, briefly describe the therapeutic approaches, including changes in lifestyle and current pharmacological interventions to manage these lipid alterations aimed at preventing CV events.